Non-Isothermal Decomposition of 2-(2-Hydroxybenzylideneamino)-3-phenylpropanoic Acid in Nitrogen Atmosphere - M. Vennila; G. Manikandan; V. Thanikachalam; J. Jayabharathi (E-Journal of Chemistry)
The non-isothermal decomposition properties of 2-(2-hydroxy- benzylideneamino)-3-phenylpropanoic acid [HBAPPA] have been studied using microanalysis, FT-IR, UV, DTA, DTG and TG techniques. The TG studies were carried out at different heating rates of 10, 15 and 20 K/min. The Schiff base decomposed in three stages. The kinetic parameters were deduced for each stage. A probable mechanism has been proposed for the decomposition process.